Effect of alloying elements in melt spun Mg-alloys for hydrogen storage - Rozenberg, Silvia (2016)
In this paper we report the effect of alloying elements on hydrogen storage properties of melt-spun Mg-based alloys. The base alloys Mg90Si10, Mg90Cu10, Mg65Cu35 (at%) were studied. We also investigated the effect of rare earths (using MM: mischmetal) and Al in Mg65Cu25Al10, Mg65Cu25MM10 and Mg65Cu10Al15MM10 alloys. All the melt-spun alloys without MM show a crystalline structure, and the Mg65Cu25MM10 and Mg65Cu10Al15MM10 alloys showed an amorphous and partially amorphous structure respectively. At 350˚C all the alloys had a crystalline structure during the hydrogen absorption-desorption tests. It was observed that Si and Cu in the binaries alloys hindered completely the activation of thehydrogen absorption. The partial substitution of Cu by MM or Al allowed activation. The combined substitution of Cu by MM and Al showed the best results with the fastest absorption and desorption kinetics, which suggests that this combination can be used for new Mg-alloys to improve hydrogen storage properties.